IMAGE OF TRAVEL IN MODERN GENRE PAINTING CHINA - ФЕЙ, М. (Art and Design, 2023)
The purpose of the article is to understand the stylistic, compositional and coloristic solutions of creating the image of a journey in modern genre painting of China. Methodology. The research methodology is based on the use of both general scientific methods of analysis and special art-scientific methods, namely: methods of formal-stylistic and compositional-coloristic analysis. The results. On the examples of the analysis of the paintings of Zhou Zongkai, Zhao Xiaodong, Wang Rusi, and Du Haijun, the artistic features of the embodiment of the image of travel in modern Chinese genre painting are revealed. The semantic connotations related to the concept of "journey" are revealed, and how these connotations are expressed in modern Chinese easel painting is analyzed. The stylistic, compositional and coloristic solutions of creating the image of travel in modern genre painting of China are understood, and it is proved that the main stylistic direction of the representation of the image of travel is realism, a style that supports or restores referential connections with reality, with the culture of everyday life in China. Various meaningful modes of the image of travel in modern genre painting of China are characterized, the scenario event of this image is revealed, which is connected with ecology, climate, problems of labor migration, festive culture of the country, etc.. It is proved that by reproducing mono-figure and multi-figure compositions, modern artists genre artists not only use a certain experience of mastering the laws of Western oil painting, but also try to find their own compositional constructions and coloristic means of artistic expression. Scientific novelty. For the first time, the artistic features of the embodiment of the image of the journey in modern Chinese genre painting are determined using the examples of paintings by Zhou Zongkai, Zhao Xiaodong, Wang Rusi, and Du Haijun, created at the end of the 20th and beginning of the 21st centuries. The practical significance of the obtained results lies in the possibility of their application for professional art education both in Ukraine and in China. The study opens the perspective of studying other images of everyday life in modern Chinese genre painting.